PENGARUH GAYA KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PT. NUSA KONSTRUKSI ENJINIRING - Harry Kurniawan (JURNAL PUNDI, 2020)
Fast traslate Icon translate     Fast traslate Icon translate This 1study1 aims1 to  determine  the 1influence  of  leadership  and  organization culture  on  performance of employee in PT. Nusa Konstruksi Enjiniring Tbk. The methode of  analysis used in this study is a descriptive statistical analysis and using a quantitative approach. Collecting data using questionnaires and surveys with sampling by random sampling from a population where 54 employees, the sample used is as much as 54 respondents. Prior to test the hypothesis, the data of respondents through some statistical data processing, among others: the validity and reliability of  data,  such assumption;  test  for  normality, homoskedastisitas test,  and  multicollinearity  test.  Then proceed with the analysis of the multiple liner regression and t test. And based on the result of statistical analysis, the results are as follows, namely: that the  influence  of  leadership  and  organization culture  factors has a positive effect and significant on employee performace.